2008
DOI: 10.4067/s0716-97602008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss on liver and erythrocyte polyunsaturated fatty acid pattern and oxidative stress status in obese patients with non-alcoholic fatty liver disease

Abstract: Our aim was to study the influence of weight loss on the fatty acid (FA) composition of liver and erythrocyte phospholipids and oxidative stress status in obese, non-alcoholic, fatty liver disease (NAFLD) patients. Seven obese NAFLD patients who underwent subtotal gastrectomy with a gastro-jejunal anastomosis in roux and Y were studied immediately and 3 months after surgery. Seven non-obese patients who underwent anti-reflux surgery constituted the control group. Serum F 2-isoprostane levels were measured by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…AT1 receptor blockers, used to treat hypertension, also significantly reduce IsoP levels in hyperholesterolemic patients [63]. Weight loss in obese subjects also profoundly lowers IsoP levels [64-69]. These results strongly suggest that effective interventions for CHD will either directly or indirectly lower IsoP values, so that measurement of IsoP values should be a highly useful surrogate endpoint in clinical trials.…”
Section: Isoprostanes As An Endpoint In Interventional Trialsmentioning
confidence: 99%
“…AT1 receptor blockers, used to treat hypertension, also significantly reduce IsoP levels in hyperholesterolemic patients [63]. Weight loss in obese subjects also profoundly lowers IsoP levels [64-69]. These results strongly suggest that effective interventions for CHD will either directly or indirectly lower IsoP values, so that measurement of IsoP values should be a highly useful surrogate endpoint in clinical trials.…”
Section: Isoprostanes As An Endpoint In Interventional Trialsmentioning
confidence: 99%
“…In addition, the gastrectomy improved the PUFA profile in erythrocyte membrane PLs, a change that correlated directly with that in liver PLs and approached the corresponding values of the control group. Since it is unlikely that n‐3 PUFA intake was increased following surgery, the decreased n‐6:n‐3 PUFA ratio suggests that both the intake of ALA and the conversion of ALA to n‐3 PUFAs are low in NAFLD and are involved in the mechanism of hepatic steatosis …”
Section: Evaluation Of the Nutritional Potential Of Lcn‐3 Pufas In Nafldmentioning
confidence: 98%
“…2) In a similar study, Elizondo et al . tested the hypothesis that increased oxidative stress and depleted levels of n‐3 PUFAs in hepatic and erythrocyte membrane PLs of obese NAFLD patients are ameliorated upon surgical weight loss.…”
Section: Evaluation Of the Nutritional Potential Of Lcn‐3 Pufas In Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that an increased n-6:n-3 PUFA ratio induces steatosis and inflammation, which leads to NAFLD [12]. Nutritional modification, such as increasing the n-3 PUFA proportion in the diet, can reduce the risk of obesity, inflammation, and oxidative stress and prevent the development of LS [13]. Few types of oil, such as canola oil, contain high n-3 PUFA (ALA) concentration.…”
Section: Introductionmentioning
confidence: 99%